2022
DOI: 10.1371/journal.pgph.0000935
|View full text |Cite
|
Sign up to set email alerts
|

Midwifery continuity of care: A scoping review of where, how, by whom and for whom?

Abstract: Systems of care that provide midwifery care and services through a continuity of care model have positive health outcomes for women and newborns. We conducted a scoping review to understand the global implementation of these models, asking the questions: where, how, by whom and for whom are midwifery continuity of care models implemented? Using a scoping review framework, we searched electronic and grey literature databases for reports in any language between January 2012 and January 2022, which described curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 101 publications
(132 reference statements)
0
13
0
1
Order By: Relevance
“…Regarding the lack of biological plausibility, other research studies and reviews have found reduced perinatal mortality rates and preterm birth rates for midwife-led continuity of care (MLCC) models, compared with medical-led or shared-care models (see citations in our paper and also the scoping review by Bradford and colleagues 5 ). When the World Health Organization recommended MLCC in 2016, they wrote that they made this recommendation despite the fact that “the mechanism for the probable reduction in preterm birth and perinatal death is unclear.” 6 They explain, “MLCC models are complex interventions and it is unclear whether the pathway of influence producing these positive effects is the continuity of care, the midwifery philosophy of care or both.” 6…”
mentioning
confidence: 79%
“…Regarding the lack of biological plausibility, other research studies and reviews have found reduced perinatal mortality rates and preterm birth rates for midwife-led continuity of care (MLCC) models, compared with medical-led or shared-care models (see citations in our paper and also the scoping review by Bradford and colleagues 5 ). When the World Health Organization recommended MLCC in 2016, they wrote that they made this recommendation despite the fact that “the mechanism for the probable reduction in preterm birth and perinatal death is unclear.” 6 They explain, “MLCC models are complex interventions and it is unclear whether the pathway of influence producing these positive effects is the continuity of care, the midwifery philosophy of care or both.” 6…”
mentioning
confidence: 79%
“…Several interventions have been implemented to improve continuity, for example, MCH booklets introduced in Angola 18. Previous reviews on MCH in high-income countries have also emphasised the importance of strengthening continuity, highlighting this as a priority area for research in LMICs 19…”
Section: Introductionmentioning
confidence: 99%
“…Continuity of midwifery care has become a global effort to enable women to have access to high-quality maternity care and delivery services [ 3 ]. As a result, many service providers today are transitioning to a continuous care model [ 4 ], and they have considered continuous care to be necessary for realizing women's rights [ 5 ]. Also, continuous midwifery care is known as the gold standard in maternity care to achieve excellent results for women [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Providing high quality care requires enhancing the clinical competence of the professionals [ 4 ]. There is a close relationship between the concept of patient care quality and clinical competence.…”
Section: Introductionmentioning
confidence: 99%